Dopamine receptor density and white mater integrity: 18F-fallypride positron emission tomography and diffusion tensor imaging study in healthy and schizophrenia subjects - Mitelman, Serge A.; Buchsbaum, Monte S.; Christian, Bradley T.; Merrill, Brian M.; Buchsbaum, Bradley R.; Mukherjee, Jogeshwar; Lehrer, Douglas S. (Brain imaging and behavior, 2020)
Dopaminergic dysfunction and changes in white matter integrity are among the most replicated findings in schizophrenia. A modulating role of dopamine in myelin formation has been proposed in animal models and healthy human brain, but has not yet been systematically explored in schizophrenia. We used diffusion tensor imaging and 18 F-fallypride positron emission tomography in 19 healthy and 25 schizophrenia subjects to assess the relationship between gray matter dopamine D 2 /D 3 receptor density and white matter fractional anisotropy in each diagnostic group. AFNI regions of interest were acquired for 42 cortical Brodmann areas and subcortical gray matter structures as well as stereotaxically placed in representative white matter areas implicated in schizophrenia neuroimaging literature. Welch’s t-test with permutation-based p value adjustment was used to compare means of z-transformed correlations between fractional anisotropy and 18 F-fallypride binding potentials in hypothesis-driven regions of interest in the diagnostic groups. Healthy subjects displayed an extensive pattern of predominantly negative correlations between 18 F-fallypride binding across a range of cortical and subcortical gray matter regions and fractional anisotropy in rostral white matter regions (internal capsule, frontal lobe, anterior corpus callosum). These patterns were disrupted in subjects with schizophrenia, who displayed significantly weaker overall correlations as well as comparatively scant numbers of significant correlations with the internal capsule and frontal (but not temporal) white matter, especially for dopamine receptor density in thalamic nuclei. Dopamine D 2 /D 3 receptor density and white matter integrity appear to be interrelated, and their decreases in schizophrenia may stem from hyperdopaminergia with dysregulation of dopaminergic impact on axonal myelination.